Implementasi Pancasila Sebagai Pandangan Hidup Bangsa Indonesia Dalam Kehidupan Sehari-Hari - Rahma, Arlanda Nissa; Dewi, Dinie Anggraeni (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
The purpose of this study was to find out how Pancasila was born from the Indonesian people and implemented in everyday life. The method of this research is a literature study, by researching and understanding book books regarding the theme carried by the author, such as books, journal articles, research reports, newspapers, seminar results. The results of this study are Pancasila are the identity of the Indonesian nation. Pancasila consists of a divinity of the element that believes in a religion of each and as humans must always obey God by obeying all orders and avoiding all its prohibitions, humanitarian elements as humans are created to have a fair and civilized human sense in people's lives, elements Association by upholding unified harmonious and family values ​​that have become the characteristic of the Indonesian nation, the community of people can solve problems by means of deliberation to obtain results agreed by many parties and elements of the Indonesian community justice has the same position in law, has rights and obligations the same in the life of nation and state.